Если что-то будет непонятно - спрашивай.
Объяснение:
1. ( 8x ² - 3x)( 8x ² + 3x)=
=(8x²)-(3x)=
=64-9
2. (3d+5c) ² - (3d-5c) ²=
=
3. ( 11x - 15y)( 11x+ 15y)=
Если что-то будет непонятно - спрашивай.
Объяснение:
1. ( 8x ² - 3x)( 8x ² + 3x)=
=(8x²)
-(3x)
=
=64
-9![x^{2}](/tpl/images/1331/0632/35e67.png)
2. (3d+5c) ² - (3d-5c) ²=
=![9d^{2}+30dc+25c^{2} -9d^{2} +30dc-25c^{2} =\\=30dc+30dc=\\=60dc](/tpl/images/1331/0632/566bb.png)
3. ( 11x - 15y)( 11x+ 15y)=
=![(11x)^{2} -(15y)^{2} =\\=121x^{2} -225y^{2}](/tpl/images/1331/0632/3d8af.png)